2021
DOI: 10.14745/ccdr.v47i78a02
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: A case for the collection of race data in Canada and abroad

Abstract: Racialized populations have consistently been shown to have poorer health outcomes worldwide. This pattern has become even more prominent in the wake of the coronavirus disease 2019 (COVID-19) pandemic. In countries where race disaggregated data are routinely collected, such as the United States and the United Kingdom, preliminary reports have identified that racialized populations are at a heightened risk of COVID-19 infection and mortality. Similar patterns are emerging in Canada but rely on proxy measures s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 12 publications
1
30
0
1
Order By: Relevance
“…For example, there are inequities in housing, income, employment, and education among racialized populations in Canada ( Nestel, 2012 ; Public Health Agency of Canada, 2020 ). Systemic racism rooted in public policies, practices, and institutions ( Thompson et al., 2021 ) contributes to such inequities. Thus, the layered effect of living with HIV, legal and/or immigration status, disparities in the social determinants of health among racialized immigrants living with HIV provides impetus for society to re-think public policies that promote discrimination, stigma, racism, and injustices towards racialized immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are inequities in housing, income, employment, and education among racialized populations in Canada ( Nestel, 2012 ; Public Health Agency of Canada, 2020 ). Systemic racism rooted in public policies, practices, and institutions ( Thompson et al., 2021 ) contributes to such inequities. Thus, the layered effect of living with HIV, legal and/or immigration status, disparities in the social determinants of health among racialized immigrants living with HIV provides impetus for society to re-think public policies that promote discrimination, stigma, racism, and injustices towards racialized immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that race is a social construct, investigation of adverse pregnancy outcomes across subpopulations can lead to identification of underlying systemic inequities and discrimination, which influence maternal comorbidities, environmental exposures and healthcare access [10,105,106]. Less than half of the reviewed studies reported race/ethnicity of pregnant people, with almost all of these studies (32/35) conducted in Australia, Europe or the United States.…”
Section: Social Gradient Of Riskmentioning
confidence: 99%
“…Less than half of the reviewed studies reported race/ethnicity of pregnant people, with almost all of these studies (32/35) conducted in Australia, Europe or the United States. National records of race/ethnicity healthcare and birth registry data are not universal-such that these data may not be available for collection and analysis [106]. Race/ethnicity data was often aggregated into a priori census categories [28,73,90], emphasized Indigenous status [56,63] or used immigration status as a binary, proxy category [20,39].…”
Section: Social Gradient Of Riskmentioning
confidence: 99%
“…COVID-4 19, much like HIV before it-it's 'curve flattened' except for those at the most marginalized sociodemographic intersections-has in fact highlighted the fault lines of marginalization that produce rampant health disparities. In the U.S. and Canada, COVID-19 exerts a disproportionate impact on Black/African American, Latinx, indigenous [15][16][17][18][19][20][21], and sexual and gender minority [22][23][24] communities, immigrants and refugees [25,26], incarcerated people, and people with disabilities [27]. These populations experience elevated rates of physical and mental health conditions and comorbidities owing to ongoing adverse social determinants of health (SDOH) [28]: structural inequalities, such as unstable housing and employment, residential segregation, lack of access to affordable healthcare, barriers to mobility, and systemic racism, homophobia, and transphobia.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%